Genetic and Leaf Characteristic Diversity on 10 Mutant Progenies of Patchouli (Pogostemon cablin) Provide Insights to Selection Strategies - Muhammad Tahir; Dewi Riniarti; Ersan Ersan; Jakty Kusuma (AGRIVITA, Journal of Agricultural Science, 2019)
The importance of patchouli plants to produce essential oil has established this medicinal herb as one of the Indonesia’s main economic contributor. To date, Indonesia can only provide 5 varieties i.e. Sidikalang, Tapak Tuan, Lhokseumawe, Patchoulina 1 and Patchoulina 2. In order to increase national patchouli production, several efforts needs to be done by providing new superior patchouli lines. This experiment was undertaken to reveal diversity of mutant progenies derived from gamma ray irradiation in patchouli. Six SSR primers were used to determine genetic diversity on MV3 generation of the mutants. Molecular analysis revealed a moderate to high polymorphism based on tested primers, which amplified 73 bands, and resulting of 0.705 PIC value. Dendrogram analysis based on Euclidean dissimilarity showed broad diversity that ranged from 0.23 to 0.82. Phenotypic tree gave clear separation that all mutant clones were clustered into three different group, with Eucledian dissimilarity coefficient ranging from 0.02 to 0.13. This report indicates that Patchouli vegetatively-propagated mutants were able to maintain their variability continuously from their parental lines (M0). Furthermore, our findings offer comprehensive information on breeding strategies of patchouli plants, giving an opportunity to assess important traits at early generation.